Development of the foldable comic 'Tabot Bengkulu' media to enhance cultural and civic literacy - Nady Febri Ariffiando; Atika Susanti (Universitas Sebelas Maret, 2024)
Literacy in education, particularly cultural and civic literacy, is a key priority in improving the learning process in schools. Despite various initiatives by the Ministry of Education and Culture, student literacy remains suboptimal, highlighting the need for innovative learning media. This study focuses on developing Folded Comic Media grounded in Bengkulu’s local culture to enhance students' cultural and civic literacy. Using the Borg and Gall development model, the research incorporates both qualitative and quantitative methods to evaluate the media's effectiveness. Findings indicate that the Folded Comic Media significantly improved students' literacy, with average scores increasing from 70.37% in Cycle I to 84.09% in Cycle II. These results demonstrate the potential of locally contextualized learning tools in fostering cultural awareness and citizenship among elementary school students.